Antibodies against MERS coronavirus in dromedary camels, Kenya, 1992 - 2013 - Corman, V.M.; Jores, Joerg; Meyer, B.; Younan, M.; Liljander, Anne M.; Said, Mohammed Yahya; Gluecks, Ilona V.; Lattwein, E.; Bosch, B.J.; Drexler, J.F.; Bornstein, S.; Drosten, C.; et al. (Centers for Disease Control and Prevention, 2014)
Dromedary camels are a putative source for human infections with Middle East respiratory syndrome coronavirus. We showed that camels sampled in different regions in Kenya during 1992–2013 have antibodies against this virus. High densities of camel populations correlated with increased seropositivity and might be a factor in predicting long-term virus maintenance.